PENGARUH SISTEM INFORMASI MANAJEMEN, LINGKUNGAN KERJA, DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN RSUD HAJI MAKASSAR PROVINSI SULAWESI SELATAN - Nengsi Wulandari; Dian Ekawaty; Ryryn Suryaman Prana Putra; Mohammad Ardani Samad (Institut Kesehatan Pelamonia, 2025)
RSUD Haji has used a management information system, but the management information system is not used optimally due to the lack of supporting facilities such as computers. In addition, there are several rooms that are less supportive so that the room is not good, such as the lighting is not too bright, and the facilities that are not used properly make employee performance still less than optimal. There are several employees who do not follow the organizational culture in RSUD Haji Makassar, for example arriving late, not doing the work given on time. This study aims to determine the effect of management information systems, work environment, and organizational culture on employee performance at RSUD Haji Makassar, South Sulawesi Province. This type of research is quantitative research with a cross sectional study design. This research was conducted on a sample of 232 employee respondents at the Hajj Hospital in Makassar, South Sulawesi Province. The research data was taken through a questionnaire that had been tested for validity and reliability. Data analysis techniques used univariate and multivariate analysis with multiple linear regression tests with the help of the SPSS 16 application. The results of this study indicate that there is an influence of (1) management information systems (p=0.001), (2) work environment (p=0.001), and (3) organizational culture (p=0.001) on employee performance. (4) There is an influence of management information systems, work environment, and organizational culture simultaneously (p=0.001) on the performance of employees of the Haji Makassar General Hospital, South Sulawesi Province. It is suggested to the Haji Makassar Hospital in South Sulawesi Province to further improve the management information system, work environment, and organizational culture in order to improve employee performance in carrying out tasks